Improving Reading Comprehension of Explanation Texts through Chunking Technique - Yuliana, Febi Dwi; Mardiyana, Yeni; Musrifah, Musrifah; Suryaningrum, Christine Wulandari (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2025)
This research uses the chunking technique to enhance students' reading comprehension of explanation texts. The study was performed as Classroom Action Research (CAR) with eleventh-grade students from a high school in Jember. It was done in two stages following the Kemmis and McTaggart approach, which includes planning, acting, observing, and reflecting. During the first stage, students learned the chunking technique through individual tasks. Results indicated that their reading comprehension had improved, as shown by a rise in average scores from 53.6 in the pre-test to 69.2 in the post-test. Still, some students found it hard to utilize the technique independently. In the second stage, cooperative learning and the Teaching at the Right Level (TaRL) approach were introduced to boost involvement and understanding. Students were grouped based on their skills and worked on explanation texts suited to their level. Consequently, the average score rose to 82.2. The results suggest that the chunking technique significantly enhances students' understanding of explanation texts, especially when paired with collaborative and differentiated teaching. It also encourages greater participation and self-assurance. This study concludes that chunking is an effective method for teaching reading, especially when adjusted to fit students' requirements and enhanced by organized group activities.